Ответ:
Пошаговое объяснение:
= 3a - 6 - 2a + 6 = a
-------------------------------------
= -6z - 6 + 6z - 2 = -8
-----------------------------------
= -10a - 30 - 28 + 12a = 2a - 58
-----------------------------------------------
= 4,8 - 3,6y - 4,8 + 3,6y = 0
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
= 3a - 6 - 2a + 6 = a
-------------------------------------
= -6z - 6 + 6z - 2 = -8
-----------------------------------
= -10a - 30 - 28 + 12a = 2a - 58
-----------------------------------------------
= 4,8 - 3,6y - 4,8 + 3,6y = 0